PELATIHAN KETERAMPILAN BAHASA INGGRIS ANAK-ANAK DI PANTI ASUHAN GAYATRI WIDYA MANDALA, KABUPATEN TABANAN-BALI - Kadek Ayu Ekasani; Ni Made Ayu Sulasmini; Putu Dian Yuliani Paramita; Ida Ayu Gayatri Kesumayathi; Ni Luh Diah Mirayanti; Cokorda Istri Sri Apriyani Sudarsana; I Made Gowinda; Putu Junio Figo Budiwan; Christhofer Anugrah Singgih Tio; I Putu Agus Hary Indrawan12 (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Gayatri Widya Mandala Orphanage is an orphanage that prioritizes education based on the Belief in God whose activities are related to religion, such as making ceremonial facilities (banten) and other activities that preserve local cultural wisdom. In addition, this orphanage prioritizes formal education in schools and non-formal education related to improving children's ability to communicate in English. The problem faced by this orphanage is how to make English lessons more enjoyable and not frightening. The solution given is to provide English training for the children in a fun way, namely with games and adding vocabulary, as well as correct pronunciation. The implementation method used is a survey in the field, determining the schedule of activities, preparation, explanation, training, and ending with an evaluation. The result is that the children really enjoy the training provided and actively interact with the team and it is proven that the results of the evaluation given in writing have obtained good results.